A Case Report of Phenotypic Discrepancy in Sex Determination and Implications for Genetic Testing and Counseling - Mian, Maamoon; Allen, Morgan; Tahiri, Jihane; Allen, Charla; Reddy, P. Hemachandra (Archives of Clinical and Medical Case Reports, 2025)
This case report presents an extraordinary instance of a 7-month-old male infant with an XX chromosomal pattern—a genetic configuration typically associated with females—while displaying characteristic male physical traits. This anomaly challenges established concepts of sex determination and highlights the intricate interplay between genetic factors and phenotypic expression. The aim of this report is to delve into the clinical implications of this rare presentation and to explore its broader significance for understanding human sex development. The infant's mother, a 20-yearold primigravid Caucasian woman with a medical history of type 2 diabetes managed with Metformin and significant maternal obesity (BMI = 37), underwent a comprehensive prenatal evaluation, including Natera DNA testing. Initial genetic testing revealed an XX chromosomal pattern with a low risk for chromosomal abnormalities. However, subsequent ultrasounds revealed male genitalia, leading to further investigations for congenital adrenal hyperplasia (CAH). Despite normal hormone levels and negative genetic screens for CAH, the newborn exhibited male physical characteristics at birth. This case underscores a significant discrepancy between genetic predictions and observed phenotype, highlighting the limitations inherent in current prenatal genetic testing technologies and the complexity of sex determination mechanisms. The discrepancy observed in this case underscores the critical need for a nuanced approach to genetic evaluation and counseling. It illustrates the limitations of relying solely on genetic tests to predict phenotypic outcomes and emphasizes the importance of integrating clinical, genetic, and phenotypic data in diagnostic processes. A multidisciplinary approach involving geneticists, endocrinologists, pediatricians, and genetic counselors is essential for managing such complex cases effectively. This case advocates for further research into the genetic and environmental factors influencing sex development to enhance diagnostic accuracy and refine personalized care strategies. Ultimately, this report aims to contribute to a deeper understanding of sex development anomalies, advocating for improved diagnostic practices and comprehensive patient support in addressing these rare and complex conditions.